Nilai Nafkah Istri Dalam Pandangan Ulama Klasik Dan Kontemporer - Ahmad Yani Nasution; Moh Jazuli (TERAJU: Jurnal Syariah dan Hukum, 2020)
This study entitled "The Value of a Wife's Living According to Classical and Contemporary Ulama". The discussion that is the focus of this research is about the opinions of classical and contemporary scholars about the value of a wife's living. Various problems that arise about the value of living in daily life often raise questions as to what the actual value of living is. Here are the various problems that writers get in everyday life. Namely there are differences in the ability of providers; there is a case where a husband feels that he has sufficient income, but the wife feels less and demands more; there are cases where the wife compares the income she receives with the income received by her neighbors, friends, or other people; there are cases where women also work; there are customs or habits that vary in each place; there is a difference in strata (rich / poor) between the husband of the provider and the wife who receives the bread; there is a husband who gives a lot of money which tends to be excessive to his wife so that it seems as if he does not remember tomorrow; on the other hand, there is also a husband who is too stingy with his wife. This research is a library research by examining the main data sources in the form of classical and contemporary scholarly books which contain descriptions of the value of a wife's living. The final objective of this research is to find out how the wives' income value among classical and contemporary scholars and to explain the comparison of the size of the value of living both among classical and contemporary scholars. The data that the authors collect from primary, secondary, and supporting sources will be processed in a descriptive analysis. Among the books of the four schools are Al-fiqhu 'Ala Mazahib Al-arba'ah, Durrul Mukhtar, Al-Mughni Ibn Quddamah, Al-Umm, Kifayatul Akhyar, FIqh Islam Wa Adillatuhu, Al-Umm, and other relevant books. . Then, from the existing data, it is analyzed to see its relationship with the issue of wives' living value among classical and contemporary scholars. After the opinions of all schools have been collected, they will be compared between the opinions of one school and another. Which one is the same and which one is different.